Pengujian Kualitas Air Laut di kecamatan Bahodopi, Kabupaten Morowali, Sulawesi Tengah berdasarkan nilai TDS dan TSS - Amin Siharis, Al; Amin, Fitrani; Abriansyah, Abriansyah; Aldiyansyah, Aldiyansyah; Ramadhan Shaddad, Aqsal; Zulkarnain Ladianto, Hadi; Saleh, Fitra (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2024)
Cahaya Ganda Gindi is a nickel company engaged in nickel mining. PT. Cahaya Ganda Gindi's nickel ore mining is currently in the operational stage with topsoil stripping and overburden excavation activities, laterite nickel mining, and laterite nickel transportation. There are community activities around the mining site so the environmental conditions need to be maintained and maintained so that the activities of residents in the area are not disturbed. Topsoil stripping and overburden excavation activities, as well as laterite nickel mining activities have an impact on decreasing the quality of surface water and seawater quality. This decrease in water quality is due to increased surface water flow/erosion from the mine front. The implementation of this seawater quality test is carried out by taking seawater samples at several points and then conducting laboratory tests to determine the quality of the seawater in the hope that the community will know the quality of the seawater around them so that mitigation steps can be determined if pollution exceeds the specified quality standards